Epidemiology of rare diseases detected by newborn screening in the Czech Republic - David, Jan; Chrastina, Petr; Pešková, Karolina; Kožich, Viktor; Friedecký, David; Adam, Tomáš; Hlídková, Eva; Vinohradská, Hana; Novotná, Dana; Hedelová, Monika; Al Taji, Eva; Holubová, Andrea; et al. (Central European journal of public health, 2019)
OBJECTIVES: Presymptomatic detection of patients with rare diseases (RD), defined by a population frequency less than 1 : 2,000, is the task of newborn screening (NBS). In the Czech Republic (CZ), currently eighteen RD are screened: phenylketonuria/hyperphenylalaninemia (PKU/HPA), congenital hypothyroidism (CH), congenital adrenal hyperplasia (CAH), cystic fibrosis (CF), medium chain acyl-CoA dehydrogenase deficiency (MCADD), long chain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD), very long chain acyl-CoA dehydrogenase deficiency (VLCADD), carnitine palmitoyl transferase I and II deficiency (CPTID, CPTIID), carnitine-acylcarnitine translocase deficiency (CACTD), maple syrup urine disease (MSUD), glutaric aciduria type I (GA I), isovaleryl-CoA dehydrogenase deficiency (IVA), argininemia (ARG), citrullinemia (CIT), biotinidase deficiency (BTD), cystathionine beta-synthase-deficient homocystinuria (CBSD HCU), and methylenetetrahydrofolate reductase deficiency homocystinuria (MTHFRD HCU). The aim was to analyze the prevalence of RD screened by NBS in CZ. METHODS: We examined the NBS programme in CZ from 1 January 2010 to 31 December 2017, which covered 888,891 neonates. Dried blood spots were primarily analyzed using fluorescence immuno-assay, tandem mass spectrometry and fluorimetry. RESULTS: The overall prevalence of RD among the neonate cohort was 1 : 1,043. Individually, 1 : 2,877 for CH, 1 : 5,521 for PKU/HPA, 1 : 6,536 for CF (1 : 5,887 including false negative patients), 1 : 12,520 for CAH, 1 : 22,222 for MCADD, 1 : 80,808 for LCHADD, 1 : 177,778 for GA I, 1 : 177,778 for IVA, 1 : 222,223 for VLCADD, 1 : 296,297 for MSUD, 1 : 8,638 for BTD, and 1 : 181,396 for CBSD HCU. CONCLUSIONS: The observed prevalence of RD, based on NBS, corresponds to that expected, more precisely it was higher for BTD and lower for MSUD, IVA, CBSD HCU, MCADD and VLCADD. Early detection of rare diseases by means of NBS is an effective secondary prevention tool.
Keywords: novorozenec; Infant, Newborn; Fluorometry; Humans; public health; Tandem Mass Spectrometry; Rare Diseases; rare disease; prevention; Neonatal Screening; lidé; Biomarkers; novorozenecký screening; tandemová hmotnostní spektrometrie; newborn screening; biologické markery; epidemiology; fluorometrie; Czech Republic; Česká republika; vzácné nemoci